(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The controversial inclusion of traditional food coming from Third Countries in the category of Novel Food, as defined by EU Regulation 258/97, caused a severe eco-nomic, social as well as environmental impact, especially for small producers in Developing Countries. The paper aims at analyzing these criticalities and the reactions of Third States, also at the WTO level, then focusing on the solutions included in the current EU Reg. 2015/2283: the European legislator has adopted a specific and simplified authorization procedure for this particular Novel Food’s category in order to assess a correct and proportionate balance between market, sustainable development, food safety and consumers’ protection.